2008
DOI: 10.1056/nejmoa062800
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Abnormalities and Sudden Death in Myotonic Dystrophy Type 1

Abstract: Patients with adult myotonic dystrophy type 1 are at high risk for arrhythmias and sudden death. A severe abnormality on the ECG and a diagnosis of an atrial tachyarrhythmia predict sudden death. (ClinicalTrials.gov number, NCT00622453.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
401
4
22

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 449 publications
(447 citation statements)
references
References 30 publications
20
401
4
22
Order By: Relevance
“…109 The presence of conduction defects and atrial arrhythmias are independent risk factors for sudden death. 103,110 In Emery-Dreifuss and Limb-Girdle type IB disease, widespread atrial fibrosis can lead to atrial standstill. 101 In Emery-Dreifuss, AF and atrial flutter with slow ventricular responses and asystolic pauses can be observed, coupled with the occurrence of thromboembolism and stroke.…”
Section: Hereditary Muscular Dystrophiesmentioning
confidence: 99%
“…109 The presence of conduction defects and atrial arrhythmias are independent risk factors for sudden death. 103,110 In Emery-Dreifuss and Limb-Girdle type IB disease, widespread atrial fibrosis can lead to atrial standstill. 101 In Emery-Dreifuss, AF and atrial flutter with slow ventricular responses and asystolic pauses can be observed, coupled with the occurrence of thromboembolism and stroke.…”
Section: Hereditary Muscular Dystrophiesmentioning
confidence: 99%
“…It is well established that sudden death can occur as a consequence of cardiac-conduction abnormalities in the DM1 patients. 18 However, it is not known whether the same risk applies to DM2 patients. In one series of 297 DM2 patients, sudden death occurred in four patients.…”
Section: Discussionmentioning
confidence: 99%
“…13 These ECG findings have been associated with worse patient outcome. [14][15][16][17] Thus, an abnormal ECG may be a prognostic indicator for development of future ventricular dysfunction and identify a high risk group of patients within the larger population of patients with cardiomyopathy. The mechanisms underlying conduction system abnormalities in patients with Alström syndrome are not known and potentially multi-factorial.…”
Section: Discussionmentioning
confidence: 99%